2003
DOI: 10.1021/es0206184
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of Polycyclic Aromatic Hydrocarbons in the Urban Atmosphere:  A Comparison of Three Methods

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous pollutants in urban atmospheres. Several PAHs are known carcinogens or are the precursors to carcinogenic daughter compounds. Understanding the contributions of the various emission sources is critical to appropriately managing PAH levels in the environment. The sources of PAHs to ambient air in Baltimore, MD, were determined by using three source apportionment methods, principal component analysis with multiple linear regression, UNMIX, and positive matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
528
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,174 publications
(549 citation statements)
references
References 37 publications
15
528
1
5
Order By: Relevance
“…Several previous studies [30][31][32] have reported the utility of multivariate linear regression to apportion sources of organic pollutants in various environmental matrices. The framework (Fig.…”
Section: Assessment Of the Degree Of Wastewater Treatmentmentioning
confidence: 99%
“…Several previous studies [30][31][32] have reported the utility of multivariate linear regression to apportion sources of organic pollutants in various environmental matrices. The framework (Fig.…”
Section: Assessment Of the Degree Of Wastewater Treatmentmentioning
confidence: 99%
“…Chemical mass balance (CMB) model has been widely used to estimate the source contributions to ambient pollutants (Larsen and Baker 2003;Lee et al 2008). However, there are certain limitations in this model such as requiring the input of unique profile for each major source (Robinson et al 2006;Shrivastava et al 2007;van Drooge and Ballesta 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several factor-based approaches have been used, including principal component analysis (PCA) followed by multiple linear regression (MLR) (Larsen and Baker, 2003), positive matrix factorization (PMF) (Paatero and Tapper, 1994) and UNMIX (Henry, 2000). UNMIX has been recently utilized to establish ambient aerosol sources and was reported to provide good agreement with predictions of other multivariate receptor models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…UNMIX has been recently utilized to establish ambient aerosol sources and was reported to provide good agreement with predictions of other multivariate receptor models (e.g. PCA/MLR, PMF), especially in identifying the dominant source categories (Henry, 2000;Lewis et al, 2003;Larsen and Baker, 2003;Maykut et al, 2003;Mukerjee et al, 2004). A summary of various recent UNMIX applications are outlined in Table 1.…”
Section: Introductionmentioning
confidence: 99%